INFRASTRUCTURE BUILDING ADJUSTMENT IN THE COVID-19 PANDEMIC - Yuliana (Border: Jurnal Arsitektur, 2021)
Infrastructure building adjustment must be done during the COVID-19 pandemic to ensure the health protocol implementation. The permanent buildings cannot be changed. Therefore, the infrastructure building adjustment need to be done. There are some modifications on the places and sites, also addition of specific instrument to ensure the good air circulation. This paper aims to describe the adjustment of infrastructure building during the COVID-19 pandemic. Method: This is a narrative literature review. Articles were searched in Science Direct, PubMed, and Google Scholar. The articles were selected based on title, abstract, and full-text screening. Results of literature review revealed that the buildings should have at least an air purifier as filter and open windows to ensure the good airflow. The recirculated air from the surrounding people without circulation increases the risks of COVID-19 transmission. Joining rooms such as joined kitchens or living rooms must not be used during this time. If the room is very important and must be used together, then there should be a break period from one user to another user. This break time is important to allow fresh air circulation. The important factors in building adjustment and modification are cost, health aspects, function, and the users’ safety. In conclusion, the adjustment of infrastructure building during the COVID-19 pandemic can be implemented by maintaining the good air circulation flow in the room, using an air purifier as filter, and ensuring a break period for users in using joining rooms.